PENDAMPINGAN AKTIVITAS OLAHRAGA REKREASI ARUNG JERAM PODUWOMA PADA MAHASISWA PENELITI WISATA OLAHRAGA - Pomatahu, Aisah R; Pauweni, Mirdayani; Syam, Asry; Parengkuan, Meyke; Lamusu, Zulkifli; Pakaya, Rosbin; Ikhsan, Haerul (Jambura Arena Pengabdian, 2024)
Recreational activities can be defined as refreshing, re-energising physically and mentally through activities that are different from the routine. Recreational activities that involve sports are called recreational sports, while recreational sports carried out at tourist sites are called sports tourism. This service activity aims to monitor recreational rafting sports activities in research students, and assist students in collecting data on poduwoma rafting tourism. The activity stages consist of: preparation, implementation, and evaluation. Based on the evaluation at the end of the activity, participants only went through 1 rapids from the usual route of 5 rapids.